Some Coal Deposits of the Peace River Foothills, British Columbia: - McLearn, Frank Harris, 1885-1964 (Author); Geological Survey of Canada (Author) (Geological Survey of Canada, 1944)
F.H. McLearn and E.J.W. Irish. Paper (Geological Survey of Canada) 44-15.